Multi-Scale Assessment Of Coal And Gas Outbursts Based On Fractal Measurements - Mingju Liu (International Conference on Ground Control in Mining, 2000)
In this research, we measured fractal characteristics of over ten typical outburst areas on different scales and related them to their outburst proneness, in attempts to provide new methods for outburst prediction. It was shown that both faults and folds follow the power law on coal basin scale, mine scale or mining district scale, whichever it is. Fractal dimensions are appropriate indices to describe geological structures quantitatively. Preliminary relationships have been established between outburst proneness and fractal dimension. Comparisons have been made among fractal characteristics and degrees of outburst proneness on all three scales. The results indicate that multi-scale assessment of outburst proneness can be made based on fractal measurements independently or supplemented by other assessment methods.